Education Levels among Parents and Misconceptions on HIV and AIDS - Masanja, Methusela Mishael (Asian Business Review, 2014)
This study investigated the association between Parents’ education levels and beliefs towards HIV/AIDS and People Living with HIV and AIDS (PLWHA). Data was collected using a set of questionnaire. Five points Likert was used to measure parents’ attitudes and beliefs towards HIV/AIDS and PLWHA. Findings from this study show that age, sex, religion, and occupations had no significant influence on beliefs but differences in education level exerted difference in beliefs of respondents towards HIV and AIDS and PLWHA (p = 0.010). Misconceptions and negative beliefs towards HIV/AIDS and PLWHA among parents with no formal education should be fought.
Keywords: Education level; HIV; AIDS; Beliefs